Understanding the Solution-Phase Growth of Cu and Ag Nanowires and Nanocubes from First Principles - Fichthorn, Kristen A (Langmuir : the ACS journal of surfaces and colloids, 2021)
In this feature article, we provide an account of the Langmuir Lecture delivered by Kristen Fichthorn at the Fall 2020 Virtual Meeting of the American Chemical Society. We discuss how multiscale theory and simulations based on first-principles DFT were useful in uncovering the intertwined influences of kinetics and thermodynamics on the shapes of Ag and Cu cubes and nanowires grown in solution. We discuss how Ag nanocubes can form through PVP-modified deposition kinetics and how the addition of chloride to the synthesis can promote thermodynamic cubic shapes for both Ag and Cu. We discuss kinetic factors contributing to nanowire growth: in the case of Ag, we show that high-aspect-ratio nanowires can form as a consequence of Ag atom surface diffusion on the strained surfaces of Marks-like decahedral seeds. On the other hand, solution-phase chloride enhances Cu nanowire growth due to a synergistic interaction between adsorbed chloride and hexadecylamine (HDA), which leaves the {111} nanowire ends virtually bare while the {100} sides are fully covered with HDA. For each of these topics, a synergy between theory and experiment led to significant progress